Supraventricular Tachycardia Conversion as a Response in Ventricular Premature Complexes - Konstantinos Tampakis, MD; Evangelia-Erasmia Papakonstantinou, MD; Alexandros Sykiotis, MD; Sokratis Pastromas, MD; George Andrikopoulos, MD (JACC: Case Reports, 2025)
In 3 similar cases of supraventricular tachycardia, rhythm presented the same conversion mode. In 1 case, tachycardia was terminated with atrial activation, while entrainment maneuvers during an electrophysiology study revealed the same response and diagnosis in all 3 cases. What is the most likely underlying mechanism of these tachycardias?